THE IMPLEMENTATION OF GOOD CORPORATE GOVERNANCE AND EFFORTS TO PREVENT FRAUD IN BANKING COMPANIES - Endah, Nur; Tarjo, Tarjo; Musyarofah, Siti (Jurnal Reviu Akuntansi dan Keuangan)
To realize good corporate governance, the principles of transparency, accountability, responsibility, independence, and fairness must be implemented to the fullest. The purpose of this study is to determine how the implementation of Good Corporate Governance and efforts to prevent fraud in banking companies. The research method used is a qualitative method. The data sources are primary and secondary data. The data is collected by interview, observation, and documentation. Whereas the data analysis technique is done by data reduction, data presentation, and drawing conclusions. The results of the study show that the application of GCG at PT. BPR X can be said to be done according to the rules, but it is not yet optimal, it can be seen from several problems that exist in the company. The maximum implementation of GCG is expected to prevent fraud in banking companies.